Detection of disseminated tumor cells from the bone marrow of patients with early breast cancer is associated with high 21-gene recurrence score - Hartkopf, Andreas; Wallwiener, Markus; Kommoss, Stefan; Taran, Florin-Andrei; Brucker, Sara Y. (Breast cancer research and treatment, 2016)
High 21-gene recurrence score (RS) is associated with an impaired prognosis in patients with HR-positive/HER2-negative early breast cancer (EBC) and predictive of response to adjuvant chemotherapy. Detection of disseminated tumor cells (DTCs) in the bone marrow is a surrogate of minimal residual disease and of prognostic value. The aim of this study was to compare DTC detection with the 21-gene RS. DTCs were identified in bone marrow aspirates of HR-positive/HER2-negative EBC patients by immunocytochemistry (pancytokeratin antibody A45-B/B3) and cytomorphology at primary surgery. The 21-gene RS was assessed in paraffin-embedded tumor tissue samples using Oncotype DX (Genomic Health). A total of 114 patients were included in this study. DTCs were detected in 13 of these (11 %). Of the women with a low RS (<18), 5/75 (7 %) were DTC positive. Of the women with an intermediate/high RS (≥18), 8/39 (21 %) were DTC positive (p = 0.03, Chi-squared test). The median RS in DTC-negative patients was significantly lower as compared to DTC-positive patients (15 vs. 20, p = 0.04, Mann-Whitney U test). In conclusion, detection of DTCs in patients with EBC is associated with high 21-gene recurrence score. These findings are meaningful for further basic research that aims to investigate the biological mechanism of tumor cell spread and cancer progression and may have prognostic and/or predictive clinical implications that should be evaluated in future clinical trials.
Gesehen am 30.04.2020